2010
DOI: 10.1111/j.1468-4446.2010.01325.x
|View full text |Cite
|
Sign up to set email alerts
|

The stranded individualizer under compressed modernity: South Korean women in individualization without individualism

Abstract: South Korean families have functioned as a highly effective receptacle for the country's highly compressed conditions of modernity and late modernity. It is as much due to the success of South Korean families as an engine of compressed modernity as due to their failure that they have become functionally overloaded and socially risk-ridden. Such familial burdens and risks are particularly onerous to South Korean women because of the fundamentally gender-based structure of family relations and duties that has in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Due to those changes and the extended access to Western-based information (e.g., provided by literature, the Internet, and media) it is assumed that Korean caregivers' parenting is influenced by modernization and adaptation to Western parenting beliefs (Park and Cheah, 2005; Cheah and Park, 2006). Nonetheless, traditional Korean values continue to be preserved (Kim et al, 2005; Park and Cheah, 2005; Schwarz et al, 2005; Chang and Song, 2010; Choi et al, 2013). …”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to those changes and the extended access to Western-based information (e.g., provided by literature, the Internet, and media) it is assumed that Korean caregivers' parenting is influenced by modernization and adaptation to Western parenting beliefs (Park and Cheah, 2005; Cheah and Park, 2006). Nonetheless, traditional Korean values continue to be preserved (Kim et al, 2005; Park and Cheah, 2005; Schwarz et al, 2005; Chang and Song, 2010; Choi et al, 2013). …”
Section: The Present Studymentioning
confidence: 99%
“…As the study by Park et al (2012) indicates both reactive as well as proactive sensitivity can be found in South Korean mothers. According to the notion that South Korea is subject to “Westernization” (e.g., Kim et al, 2005; Chang and Song, 2010) but that traditional Korean values still prevail (e.g., Park and Cheah, 2005; Schwarz et al, 2005; Chang and Song, 2010), it is fruitful to compare Korean mothers to mothers living in a Western context in order to elaborate the understanding of sensitivity in cultural context. Therefore, the objective of the present study is not only to investigate cultural differences but also to delineate similarities with regard to mothers' sensitivity and parenting beliefs.…”
Section: The Present Studymentioning
confidence: 99%
“…Family norms and the degree of pressure to abide by them differ by gender and age (Chang and Song 2010;Kim 2013). In general, women are expected to abide by norms governing marriage and coresidency more strongly than are men (Jamieson and Simpson 2013).…”
Section: Control Variablesmentioning
confidence: 99%
“…In Korea, family norms and the pressure to abide by them differ across gender and age (Chang and Song 2010;Kim 2013). For example, the norms of marriage and family coresidency are more strongly enforced for women than they are for men.…”
Section: Figure 1: Odds Ratios From the Ordered Logistic Regression Amentioning
confidence: 99%
“…Fourth, the 2000s also saw changes in women's attitudes to family and marriage. Younger generations of women have gradually rethought the rigid patriarchal prescription of women's roles in the family and in assisting their husband's career (Chang and Song 2010). Moreover, the view that people should have a child once they marry weakened substantially after 1997, as the data for married women analyzed by Kim and Yoo (2016) indicates.…”
Section: Discussionmentioning
confidence: 89%